Outcomes of Hospitalized COVID-19 Patients by Risk Factors: Results from a United States Hospital Claims Database - Peter J. Mallow; Kathy W. Belk; Michael Topmiller; Edmond A. Hooker (Journal of Health Economics and Outcomes Research)
**Background/Objective:** The primary objective was to quantify the role of the number of Centers of Disease Control and Prevention (CDC) risk factors on in-hospital mortality. The secondary objective was to assess the associated hospital length of stay (LOS), intensive care unit (ICU) bed utilization, and ICU LOS with the number of CDC risk factors.